An adjuvant compound that enhances immunogenicity at fractional doses of the Sabin‐inactivated poliovirus vaccine (sIPV) with a long duration of protection in a rat model. Issue 1 (9th October 2018) - Song, Shaohui; Liu, Ze; Zhou, Jian; Cai, Wei; Yang, Huijuan; Ma, Lei; Gao, Jingxia; Li, Weidong; Liao, Guoyang
Abstract: Background: At the same dosage, the new generation of Sabin‐inactivated poliovirus vaccine (sIPV) is less immunogenic than the traditional oral polio vaccine (OPV) dosage in China. The useful adjuvant might be a necessary strategy to strengthen the immune protective effects. Methods: In this study, we produced an adjuvant compound (named KML05) that could promote immunogenicity and fractional doses of sIPV with a long duration of protection in a rat model. The compound adjuvant had both advantages and a function of MF59 and carbopol971P. Results: The effect seroconversion of experimental animals immunized with KML05 could be extended to one‐eighth of the dose. According to the result of the geometric mean titers (GMTs), KML05 adjuvant could save eight times the amount of sIPV D‐antigen usage, but aluminum hydroxide adjuvant could save twice at the same titers. Additionally, it was found that there was a significant difference in the GMT titer of poliovirus type 2 between animals immunized by KML05 and alum adjuvant ( P  < 0.05). At 12th‐month postvaccination, the neutralization titers stimulated by IPV‐KML05 were maintained over a longer time period in immunized animals. Conclusion: Our research team developed KML05 adjuvant, which combined carbopol971P with MF59, increased antibody responses to sIPV for a longer duration of protection in a rat model.